Yellow Wine Polyphenolic Compounds prevents Doxorubicin‐induced cardiotoxicity through activation of the Nrf2 signalling pathway. Issue 9 (21st June 2019) - Lin, Hui; Zhang, Jie; Ni, Tingjuan; Lin, Na; Meng, Liping; Gao, Feidan; Luo, Hangqi; Liu, Xiatian; Chi, Jufang; Guo, Hangyuan
Abstract: Doxorubicin (DOX) is considered as the major culprit in chemotherapy‐induced cardiotoxicity. Yellow wine polyphenolic compounds (YWPC), which are full of polyphenols, have beneficial effects on cardiovascular disease. However, their role in DOX‐induced cardiotoxicity is poorly understood. Due to their antioxidant property, we have been suggested that YWPC could prevent DOX‐induced cardiotoxicity. In this study, we found that YWPC treatment (30 mg/kg/day) significantly improved DOX‐induced cardiac hypertrophy and cardiac dysfunction. YWPC alleviated DOX‐induced increase in oxidative stress levels, reduction in endogenous antioxidant enzyme activities and inflammatory response. Besides, administration of YWPC could prevent DOX‐induced mitochondria‐mediated cardiac apoptosis. Mechanistically, we found that YWPC attenuated DOX‐induced reactive oxygen species (ROS) and down‐regulation of transforming growth factor beta 1 (TGF‐β1)/smad3 pathway by promoting nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) nucleus translocation in cultured H9C2 cardiomyocytes. Additionally, YWPC against DOX‐induced TGF‐β1 up‐regulation were abolished by Nrf2 knockdown. Further studies revealed that YWPC could inhibit DOX‐induced cardiac fibrosis through inhibiting TGF‐β/smad3‐mediated ECM synthesis. Collectively, our results revealed that YWPC might be effective in mitigating DOX‐induced cardiotoxicity by Nrf2‐dependent down‐regulation of the TGF‐β/smad3 pathway.